Planeación Financiera a la Empresa “Delaroma S.A” de la Ciudad de Loja, Período 2022-2026. - Gallegos Cumbicos, Geidy Yanina (2023)
This Curricular Integration Work called: "Financial Planning for Delaroma S.A. Company in the city of Loja, period 2022-2026" has been carried out to fulfil the proposed objectives, implement the use of financial tools according to the needs and economic activity of the company, to minimize future risks that may arise and take advantage of opportunities to increase its profitability in the coming years. To fulfil the proposed objectives, first, we interviewed the manager and the accountant to gather the necessary information regarding the Financial Statements for the year 2021 to be able to make the financial indicators and proceed to develop the sales and purchases forecasts for the proposed five years; for sales, we used a percentage of 6.85% and for purchases a rate of 5.82%; with these results we developed the Cash Flow also known as Cash Budget, where can be used the final balance to reinvest in the company, allowing it to obtain increased benefits. Once we determined the results of the Cash Flow, we can prepare the Proforma Income Statement and the Proforma Statement of Financial Position for the period 2022 to 2026 to know what the future income, costs, and expenses will be in addition to providing a perspective of the financial situation that the company will obtain. We also considered it appropriate to prepare a report of the most relevant results of the Financial Planning; to inform the managers of the company DELAROMA Public Limited Company what the future economic-financial situation of the company would be, which will allow them to make the right decisions.